The effectiveness of a value-based EMOtion-cognition-Focused educational programme to reduce diabetes-related distress in Malay adults with Type 2 diabetes (VEMOFIT): study protocol for a cluster randomised controlled trial - Chew, Boon-How; Vos, Rimke C.; Ghazali, Sazlina Shariff; Shamsuddin, Nurainul Hana; Fernandez, Aaron; Mukhtar, Firdaus; Ismail, Mastura; Ahad, Azainorsuzila Mohd; Sundram, Narayanan N.; Ali, Siti Zubaidah Mohd; Rutten, Guy E. H. M. (BMC, 2017)
Background: Type 2 diabetes mellitus (T2DM) patients experience many psychosocial problems related to their diabetes. These often lead to emotional disorders such as distress, stress, anxiety and depression, resulting in decreased self-care, quality of life and disease control. The purpose of the current study is to evaluate the effectiveness of a brief value-based emotion-focused educational programme in adults with T2DM on diabetes-related distress (DRD), depressive symptoms, illness perceptions, quality of life, diabetes self-efficacy, self-care and clinical outcomes. Methods: A cluster randomised controlled trial will be conducted in 10 public health clinics in Malaysia, all providing diabetes care according to national clinical practice guidelines. Patients’ inclusion criteria: Malay, ≥ 18 years with T2DM for at least 2 years, on regular follow-up with one of three biomarkers HbA1c, systolic blood pressure and LDL-cholesterol sub-optimally controlled, and with a mean 17-item Diabetes Distress Scale (DDS-17) score ≥ 3. The intervention consists of four sessions and one booster over a period of 4 months that provide information and skills to assist patients in having proper perceptions of their T2DM including an understanding of the treatment targets, understanding and managing their emotions and goal-setting. The comparator is an attention-control group with three meetings over a similar period. With an estimated intra-cluster correlation coefficient ρ of 0.015, a cluster size of 20 and 20% non-completion, the trial will need to enroll 198 patients. Primary outcome: the between groups difference in proportion of patients achieving a mean DDS-17 score < 3 (non-significant distress) at 6 months post-intervention. Secondary outcomes will be the differences in the above mentioned variables between groups. Discussion: We hypothesize that primary and secondary outcomes will improve significantly after the intervention compared to the comparator group. The results of this study can contribute to better care for T2DM patients with DRD.